Gender differences in availability, internet access and rate of usage of computers among distance education learners - Hanafi Atan; Fauziah Sulaiman; Zuraidah Abdul Rahman; Rozhan Mohd. Idrus (Taylor and Francis, 2002)
This study explores the level of availability of computers, Internet accessibility and the rate of usage of computers both at home and at the work place between distance education learners according to gender. The results reveal that there are no significant differences in all three aspects. The findings indicate that female distance education learners participate equally with their male counterparts in the utilization of computer technology to assist their study requirements as well as in their involvement in information and communication technology (ICT) to support the educational and learning process as demanded by distance education.